(untitled) (Clinics, 2007)
INTRODUCTION: Previous studies have detected the presence of anti-endothelial cell antibodies (AECA) in patients with Behçet's disease (BD). However, no real evidence exists whether these antibodies exert any influence on clinical presentation and/or activity of this disease. OBJECTIVES: To determine the frequency of AECA in patients with BD and analyze possible clinical associations. METHODS: 50 patients with BD who fulfilled diagnostic criteria were selected. Thirty-seven patients were females, and 13 were males; the mean age was 44 ± 9 years with a mean follow-up time of 10 ± 7.5 years. AECA were assayed by ELISA using ECV-304 cells as the antigenic substrate. The prevalence of AECA was determined, and their possible relationships with present and past clinical features were investigated. RESULTS: AECA were detected in the sera of 38% of the patients (IgG in 13, IgM in four, and IgG plus IgM in two). An association was observed between AECA and a previous history of central nervous system involvement (OR= 5.4, p= 0.03). This association was more evident for IgG-AECA (OR= 6.0, p= 0.02). A trend of an increased risk of aneurysms was also observed in patients with IgG-AECA (OR= 2.58, p= 0.77). None of the other clinical characteristics showed a relevant association with these antibodies. CONCLUSION: Our data suggest that IgG-AECA may be a marker of more severe lesions in patients with BD based on the higher frequency of previous central nervous system manifestations in patients who presently display circulating AECA.